Arguing to theism from consciousness - Page, BT (Society of Christian Philosophers, 2020)
I provide an argument from consciousness for God’s existence. I first consider a version of the argument which is ultimately difficult to evaluate. I then consider a stronger argument, on which consciousness, given our worldly laws of nature, is rather substantial evidence for God’s existence. It is this latter argument the paper largely focuses on, both in setting it out and defending it from various objections.